Exportación de granos de cacao finos de aroma hacia Alemania - Mena Morán, Esteban Vladimir (2017)
Germany is one of the countries with the highest per capita consumption of chocolate globally; however, there is no possibility of planting and harvesting its main ingredient cocoa within the country, it is important to note that there is a growing interest of people by organic products and of better quality. The present project consists of a business plan for the export of fine aroma cocoa beans to Germany in which feasibility is analyzed and if it is a profitable project. This study will analyze all the requirements, as well as processes to follow to achieve a successful export. Through market research, it was determined that there is good acceptance of the product in the city of Hamburg, specifically with the GEPA industry. The product is mainly directed to the production of different cocoa derivatives, which are marketed under the brand. The general strategy is based on the differentiation, and in a positioning more for the type of Ecuadorian cacao offered and as strategy of internationalization chosen is the direct export, which will allow us greater control of documents and costs. Finally, after realizing this project it was possible to verify that it is feasible the export of fine cocoa beans of aroma to Germany, being that all the processes besides the necessary requirements have been detailed and verified. We can also verify that it is very profitable since it generates a net profit of 28%.